Carcinogenic drug exposure among health-sector workers: the need for exposure assessment and surveillance - Claudio Müller-Ramírez; Sammy Almashat; Joanna Gaitens; Melissa McDiarmid (Pan American Health Organization, 2023)
Antineoplastic drugs (ANDs) used for chemotherapy can cause secondary cancers in treated patients and can pose carcinogenic risks to health-sector workers anywhere along these drugs' life cycle in a facility, from production to patient administration. Several PAHO/WHO Collaborating Centers (CCs) have experience addressing these hazards in the health sector. The objectives of this report are four-fold: 1) Provide an overview of longstanding research and prevention efforts, led by PAHO/WHO and its Occupational Health CCs, aimed at reducing the burden of occupational cancer in the Americas; 2) Discuss how robust AND exposure assessment and educational/outreach work by PAHO CCs can form the basis of exposure mitigation efforts among health-sector workers; 3) Through the presentation of original AND exposure assessment data from a pharmaceutical compounding facility in Chile, highlight relatively inexpensive methods by which such data can be generated; and 4) Discuss how effective, periodic environmental surveillance in healthcare facilities results in the identification of AND contamination in the work environment and enables the implementation of low-cost, high-impact interventions to reduce the risk of occupational cancer in health-sector workers, including in limited-resource settings. The risk of health-sector worker exposure to ANDs and other hazardous drugs is an important issue for inclusion within PAHO/WHO's broader efforts at reducing the impact of occupational cancer in the Americas. This report demonstrates that a wide range of accessible AND-exposure mitigation strategies are feasible at both a facility and a national policy level across the hemisphere.